Radiologic and histopathologic review of rare benign and malignant breast diseases - Dağıstan, Emine (Diagn Interv Radiol, 2017)
High social awareness of breast diseases and the rise in breast imaging facilities have led to an increase in the detection of even rare benign and malignant breast lesions. Breast lesions are associated with a broad spectrum of imaging characteristics, and each radiologic imaging technique reflects different characteristics of them. We aimed to increase familiarity of the radiologist with these uncommon lesions as well as correlate histopathologic findings with the radiologic imaging features of the tumors. Histopathologic examination is necessary in the evaluation of such breast lesions, particularly when radiologic images are not definitive for a specific diagnosis.